SISTEM DETEKSI WAJAH PADA OPEN SOURCE PHYSICAL COMPUTING - Sudianto, Yupit; Samopa, Febriliyan (Institute of Research and Community Outreach - Petra Christian University, 2014)
Face detection is one of the interesting research area. Majority of this research implemented on a computer. Development of face detection on a computer requires a significant investment costs. In addition to having to spend the cost of procurement of computers, is also required for operational cost such as electricity use, because the computer requires large power/watt.This research is proposed to build a face detection system using Arduino. The system will be autonomous, in other word the role of computer will be replaced by Arduino. Arduino is used is Arduino Mega 2560 with specifications microcontroller AT MEGA 2560, a speed of 16 MHz, 256 KB flash memory, 8 KB SRAM, 4 KB EEPROM. So not all face detection algorithm can be implemented on the Arduino. The limitations of memory owned by the arduino will be resolved by applying the method of template matching using the facial features in the form of a template that is shaped like a mask. Detection rate achieved in this study is 80% - 100%. Where, in the Arduino's success in identifying the face are influenced by the distance between the camera with the human face and human movement.